2015
DOI: 10.1088/0957-0233/26/8/084003
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopicallyin situtraceable heterodyne frequency-scanning interferometry for distances up to 50 m

Abstract: High-resolution saturation spectroscopy of iodine transitions at 637 nm is used to generate physically stable frequency reference markers for an interferometric absolute distance measurement based on frequency-scanning interferometry. Both experiments are performed simultaneously, posing severe challenges to the in principle well-established experimental techniques. The software-based enhancement of the signal-to-noise ratio is discussed in detail, as well as the demodulation and separation of the heterodyne i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…From Equation ( 7), we can see that when the sweeping cycle becomes small, the distance change in one sweeping cycle will also be small. At this time, take Equation (8) into Equation (7), let L dyn (T), which is the distance at the end moment T of a sweeping cycle, represent the distance after the whole sweeping cycle. It is:…”
Section: Principle Of Reducing the Doppler-induced Errormentioning
confidence: 99%
See 1 more Smart Citation
“…From Equation ( 7), we can see that when the sweeping cycle becomes small, the distance change in one sweeping cycle will also be small. At this time, take Equation (8) into Equation (7), let L dyn (T), which is the distance at the end moment T of a sweeping cycle, represent the distance after the whole sweeping cycle. It is:…”
Section: Principle Of Reducing the Doppler-induced Errormentioning
confidence: 99%
“…Warden et al [5,6] presented a dual-FSI system with a gas absorption cell to achieve dynamic OPD measurement at any sampling point. Pollinger and Liu et al [7,8] used an additional heterodyne interferometry to directly measure the target movement and used an FSI system to calculate the distance. Shao Bin et al [9] reported a fixed-frequency laser to measure the target velocity and used a FSI system to calculate the distance.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, because of the influence of noises and mode-hopping signals, some of the extreme points are incorrect (as shown in the red circle section). Thus, the parameters N and P in Equation When there are noises and mode-hopping signals in the auxiliary interferometer, Equation (3) should be rewritten as: 2πΔf(k)τ a = (π+ΔΩ(k1))k, k = 1, 2,…, N, k1 = 1, 2, …, N 1 (8) where Δ Ω (k1) is the phase deviation caused by all of the sampling points of the auxiliary interferometer output in the actual situation, and only part of the ΔΩ(k1)is caused by the erroneous sampling points is not equal to zero, while N is the number of the ideal sampling points, and N 1 is the total number of the sampling points in the actual situation. Thus, Equation (4) turns into:…”
Section: The Influence Of the Erroneous Sampling Points In The Auxilimentioning
confidence: 99%
“…. , N 1 (8) where ∆Ω(k 1 ) is the phase deviation caused by all of the sampling points of the auxiliary interferometer output in the actual situation, and only part of the ∆Ω(k 1 ) is caused by the erroneous sampling points is not equal to zero, while N is the number of the ideal sampling points, and N 1 is the total number of the sampling points in the actual situation. Thus, Equation (4) turns into:…”
Section: The Influence Of the Erroneous Sampling Points In The Auxilimentioning
confidence: 99%
See 1 more Smart Citation